2010
DOI: 10.1016/j.wpi.2009.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Towards content-based patent image retrieval: A framework perspective

Abstract: In this article, we discuss the potential benefits, the requirements and the challenges involved in patent image retrieval and subsequently, we propose a framework that encompasses advanced image analysis and indexing techniques to address the need for content-based patent image search and retrieval. The proposed framework involves the application of document image pre-processing, image feature and textual metadata extraction in order to support effectively content-based image retrieval in the patent domain. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 18 publications
0
25
0
1
Order By: Relevance
“…Within this context, several systems have been developed, including PATSEEK (Tiwari and Bansal, 2004) and PatMedia image search engine (Vrochidis et al, 2010).…”
Section: Patent Image Search and Classificationmentioning
confidence: 99%
“…Within this context, several systems have been developed, including PATSEEK (Tiwari and Bansal, 2004) and PatMedia image search engine (Vrochidis et al, 2010).…”
Section: Patent Image Search and Classificationmentioning
confidence: 99%
“…More recently, PATMEDIA 1 [26,22] has been presented. The proposed framework involves the application of document image pre-processing, image feature and textual metadata extraction to support efficient content-based image retrieval in the patent domain.…”
Section: Overview Of Research On Patent Image Retrievalmentioning
confidence: 99%
“…The patent drawing ontology created by Vrochidis et al [26], shown in Figure 3, specifies the five classes of figures that occur in patents: photo, diagram (including block, state and circuit diagrams), flowchart, technical drawing and graph. The automatic categorization of figures into pre-defined types is an initial step to enable the patent retrieval system to use the content information in the retrieval process.…”
Section: Relevant Work From Outside the Patent Domainmentioning
confidence: 99%
“…This has been extended to patent image retrieval as well. [12] and [13] propose two such systems. An image based search system called PATSEEK is detailed in [12], which uses similarity retrieval concepts to search patent documents using query images.…”
Section: Introductionmentioning
confidence: 99%
“…An image based search system called PATSEEK is detailed in [12], which uses similarity retrieval concepts to search patent documents using query images. [13] introduces indexing and image analysis techniques for patent image search and retrieval systems. Roxana Girju at Baylor University proposes a novel and innovative method [1] to automatically detect and extract causal relations from text.…”
Section: Introductionmentioning
confidence: 99%